A metacommunity ecology approach to understanding microbial community assembly in developing plant seeds - Bergmann, Gillian E.; Leveau, Johan H. J. (Frontiers in Microbiology, 2022)
Microorganisms have the potential to affect plant seed germination and seedling fitness, ultimately impacting plant health and community dynamics. Because seed-associated microbiota are highly variable across individual plants, plant species and environments, it is challenging to identify the dominant processes that underlie the assembly, composition, and influence of these communities. We propose here that metacommunity ecology provides a conceptually useful framework for studying the microbiota of developing seeds, by application of metacommunity principles of filtering, species interactions and dispersal at multiple scales. Many studies in seed microbial ecology already describe individual assembly processes in a pattern-based manner, such as correlating seed microbiome composition with genotype or tracking diversity metrics across treatments in dispersal limitation experiments. But we see a lot of opportunity to examine understudied aspects of seed microbiology, including trait-based research on mechanisms of filtering and dispersal at the micro-scale, the use of pollination exclusion experiments in macro-scale seed studies, and an in-depth evaluation of how these processes interact via priority effects experiments and joint species distribution modeling.